2017
DOI: 10.1080/10410236.2017.1339379
|View full text |Cite
|
Sign up to set email alerts
|

Adolescent Experiences of Clinician–Patient HIV/STI Communication in Primary Care

Abstract: Effective clinician–patient communication is linked to positive patient health outcomes in adults, yet the research on adolescent populations remains limited. We describe adolescent experiences of clinician–patient HIV/STI communication through qualitative interviews with predominantly African American adolescent women from a youth-centered primary care clinic. Participants described acknowledging clinicians are professionals, the importance of confidentiality to foster clinician–adolescent communication, and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
17
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
10

Relationship

3
7

Authors

Journals

citations
Cited by 24 publications
(24 citation statements)
references
References 46 publications
(64 reference statements)
0
17
0
Order By: Relevance
“…Adding a STI prevention infrastructure and capacity-building lens to the implementation of patient portals offers new strategies for addressing longstanding racial disparities. Such interventions may focus on reducing the stigma around STI health communication among youth, their sex partners, and their health care providers [6,[48][49][50]. However, the success of future interventions requires public health priorities focused on patient portal access to STI PHRs and incentives to design patient portal platforms to support sexual and reproductive health among Black youth.…”
Section: Discussionmentioning
confidence: 99%
“…Adding a STI prevention infrastructure and capacity-building lens to the implementation of patient portals offers new strategies for addressing longstanding racial disparities. Such interventions may focus on reducing the stigma around STI health communication among youth, their sex partners, and their health care providers [6,[48][49][50]. However, the success of future interventions requires public health priorities focused on patient portal access to STI PHRs and incentives to design patient portal platforms to support sexual and reproductive health among Black youth.…”
Section: Discussionmentioning
confidence: 99%
“…Saturation can be defined as reaching a point in the analytic process where no new themes emerge from the data (Bowen, 2008). Although preliminary analysis indicated that we achieved saturation, we conducted one additional focus group interview as researchers have done when conducting focus groups with adolescents (Córdova et al, 2017). The size of each focus group ranged from three to five participants.…”
Section: Methodsmentioning
confidence: 99%
“…Unfortunately, adolescent ED patients who decline HIV testing are rarely, if ever, offered a second chance to test during the same ED visit. Further, young patients are often hesitant to report risk behaviors or even discuss HIV-related issues with medical staff [ 15 , 16 ], and staff are often uncomfortable discussing sexual behavior with young patients [ 16 ], especially with sexual minority adolescents [ 17 ]. Young ED patients, especially those accompanied by their parents, are unlikely to initiate requests for HIV testing [ 18 ].…”
Section: Introductionmentioning
confidence: 99%